SCRUNTINIZING ENGLISH PROFICIENCY OF JUNIOR HIGH SCHOOL STUDENTS BASED ON CEFR - Tri Achmad Efendi; Devo Bayu Panggah Sejati (LPPM Universitas Kahuripan Kediri, 2024)
English has become one of the common tongues of the international community. Provided that fact, many English programs are offered to promote students’ English skills to prepare students facing the globalization era and workforce. Besides, to answer the 21st-century skills the government has attempted to change curriculum. However, there are still many students who are low in their English proficiency. This research was conducted to scrutinize the students’ English proficiency based on CEFR. It was done at SMPN 40 Surabaya as the population. There were 103 students from four classes of eighth grade participated in this research. The research was conducted in both quantitative and qualitative. The test using the KET (Key English Test) by Cambridge was administered to find the students’ English proficiency. However, due to the limited time, it was limited to only Listening, Reading and writing sections. Then, the results were analyzed with CEFR (Common European Framework). The result was most of the participants were at A1 for reading as well as writing while they were at A2 for listening. It means that the students understand English quite well and they can communicate in English for daily use.